2020
DOI: 10.3389/fpsyt.2020.00213
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Expectancy on Cognitive Performance, Mood, and Psychophysiology in Healthy Adolescents and Their Parents in an Experimental Study

Abstract: Objective: Placebo effects on cognitive performance and mood and their underlying mechanisms have rarely been investigated in adolescents. Therefore, the following hypotheses were investigated with an experimental paradigm: (1) placebo effects could be larger in adolescents than in adults, (2) parents' expectations influence their adolescents' expectations and placebo effects, and (3) a decrease in stress levels could be an underlying mechanism of placebo effects.Methods: Twenty-six healthy adolescents (13.8 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Importantly, we also observed a placebo-induced improvement of mood states in addition to the effects on face classification performance. Placebo effects on mood states in healthy individuals have been recently reported in some studies 44 46 while others were not able to demonstrate such effects 47 , 48 . Formal models such as the predictive coding framework 49 consider expectations as prior information, which, in a Bayesian sense, are integrated with incoming sensory information (likelihood), to form a percept (posterior) 3 , 50 .…”
Section: Discussionmentioning
confidence: 98%
“…Importantly, we also observed a placebo-induced improvement of mood states in addition to the effects on face classification performance. Placebo effects on mood states in healthy individuals have been recently reported in some studies 44 46 while others were not able to demonstrate such effects 47 , 48 . Formal models such as the predictive coding framework 49 consider expectations as prior information, which, in a Bayesian sense, are integrated with incoming sensory information (likelihood), to form a percept (posterior) 3 , 50 .…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, in both teens and young adults, it could be seen that more positive affects caused them to perform better in academics since they were more concentrated, had more attention, and could process things quicker than those who were feeling down (Science Daily, 2009). Likewise, improved memory, attention span, and a better working memory were all benefits that came to adults who experienced more positive emotions (Watolla et al, 2020;Raczy, Orzechowski, 2019). Older adults too had a better working memory when they experienced positive affect than when they experienced negative ones (Tieks et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to other studies, it was found that adults that experienced more positive affect had a much quicker reaction time to questions asked and when speaking. Moreover, these adults were able to remember a lot more things and held their attention longer than adults who did not listen to music (Watolla et al, 2020). A study in 2019 found that mood along with emotional load, had a significant effect on cognitive performance, specifically memory.…”
Section: IIImentioning
confidence: 96%
See 1 more Smart Citation
“…We analyzed the skin conductance corrected time integral or AUC (Watolla et al, 2020). This area represents the change in skin conductance over a given time interval (15 s of the target).…”
Section: Methodsmentioning
confidence: 99%